TECHNOLOGICALLY OR ECONOMICALLY OPTIMAL COMBINED INFRARED AND CONDUCTIVE DRYING OF BULK LIVE FEED - Dubrovin, A. (Енергетика і автоматика, 2016)
The combined conductive and infrared drying installation for loose forages are designed. Production is carried out in automatic mode according to technological or economic criteria.